NON-COMPETE CLAUSES IN DEALER AGREEMENTS AND VERTICAL INTEGRATION: A DOCTRINAL ANALYSIS OF THE NORMATIVE INTERACTION BETWEEN ARTICLE 14 AND ARTICLE 19 OF INDONESIAN COMPETITION LAW IN LIGHT OF KPPU DECISION NO. 18/KPPU-L/2024 (SANY TRUCK CASE) - Dian Aryani Kusady (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This research analyzes the normative ambiguity surrounding the concurrent application of Article 14 (vertical integration prohibition) and Article 19 (market control prohibition) under Indonesian Law No. 5/1999 in the context of dealer agreements with non-compete clauses. Through doctrinal legal analysis of KPPU Decision No. 18/KPPU-L/2024, which imposed Indonesia's largest competition law fine of Rp. 449 billion for simultaneous Article 14-19 violations, this study identifies substantial evidentiary overlap and legal characterization uncertainty. A comparative analysis of the competition law frameworks of Singapore, the European Union, and the United States reveals transferable principles, including market-share safe harbors, duration-based assessments of non-compete clauses, and structured foreclosure analyses. Findings demonstrate that existing Indonesian statutory provisions lack clear criteria to distinguish structural foreclosure (Article 14) from behavioral exclusion (Article 19), and that KPPU enforcement practice is inconsistent with the procedural requirements under Perkom 5/2010. The research proposes a normative clarification framework that establishes interpretive criteria for concurrent application and recommends regulatory amendments introducing market-share thresholds, a mandatory three-stage analysis, and limitations on the duration of non-compete clauses to enhance legal certainty and enforcement consistency.